POLITICAL LEGITIMACY IN AUTHORITARIAN AND DEMOCRATIC SYSTEMS – A REVIEW (International Journal of Food and Nutritional Sciences, 2022)
This study explores the Role of Political Legitimacy in Authoritarian and Democratic Systems. Political legitimacy is a crucial element in understanding the stability and effectiveness of both democratic and authoritarian systems. In democratic systems, legitimacy primarily stems from the consent of the governed, which is expressed through free and fair elections, adherence to the rule of law, protection of individual rights, and institutional checks and balances. These mechanisms ensure that power is derived from the people, maintaining a government’s credibility and accountability. The democratic model emphasizes that legitimacy is continuously earned and can be revoked based on the government's performance and adherence to democratic principles.In contrast, authoritarian regimes often derive legitimacy through alternative mechanisms. Performance-based legitimacy focuses on the regime’s ability to deliver economic growth, social stability, and public services. Ideological legitimacy is based on adherence to a particular ideology or belief system, which justifies the regime’s rule. Charismatic legitimacy centers on the personal appeal and qualities of a leader, who is seen as embodying national ideals or transformative visions. Additionally, authoritarian regimes may rely on coercive power and control, including surveillance, censorship, and repression, to maintain stability and suppress dissent.The role of political legitimacy in these systems is pivotal as it influences the government’s ability to sustain its authority and manage public perception. While democratic legitimacy is built on participatory and accountable governance, authoritarian legitimacy often depends on performance, ideology, and control. Understanding these dynamics is essential for analyzing the resilience and adaptability of different political regimes and the potential for political change or instability.